HUBUNGAN ANEMIA DAN KEKURANGAN ENERGI KRONIK PADA IBU HAMIL DENGAN BERAT BADAN BAYI BARU LAHIR - Indrasari, Oktovina Rizky (Universitas Tribhuwana Tunggadewi, 2022)
Anemia during pregnancy hurts both mother and baby. The research objective was to analyze the relationship between anemia and chronic energy deficiency in pregnant women with the incidence of new birth weight. This study used a cross-sectional research design. The population in this study were the third-trimester pregnant women in the working area of Ngadiluwih Public Health Center, Kediri Regency. The sample in this study was 52 respondents. The sampling technique used was total sampling. The results of the chi-square test showed the relationship between anemia and weight of newborns had a p-value of 0.001. It shows that there is a correlation between anemia in pregnant women and the incidence of newborn body weight with PR 21.5, which means that mothers who experience anemia during pregnancy have a 21.5 times greater risk of giving birth to babies with low birth weight than mothers who are not anemic. The association of chronic energy deficiency with newborn body weight has a p-value of 0.000. It shows that there is a relationship between chronic energy deficiency and newborn weight with PR 15.6, which means that mothers who experience chronic energy deficiency have a 15.6 times greater risk of giving birth to western babies with low birth weight than mothers who do not experience chronic energy deficiency. During pregnancy, pregnant women consume foods that contain iron and iron supplements.